# i need this answered it hurts my brain :C?

In a group of three numbers, the first number is twice the second number, and the third number is 15 less than the second number. If j is the third number and k is the sum of the first two numbers, which of the following equations represent the relationship between j and k ?

A 2j + 15 = k

B 2j + 30 = k

C 3j + 30 = k

D 3j + 45 = k

### 5 Answers

Relevance
• 3 years ago
Favorite Answer

.

let second number = x

first number is twice second number: =========>first number = 2x

third number is 15 less than the second number: =>third number = x - 15

if

(x - 15) = j

x = j + 15

( 2x ) + ( x ) = k

3x = k

x = ⅓k

Equate the two ‘x';

j + 15 = ⅓k <===> 3j + 45 = k

ANS: D

———

• ...Show all comments
• King Leo
Lv 7
3 years agoReport

It’s always better to have a better approach. If you could it would be nice to share approach.

• Login to reply the answers
• cidyah
Lv 7
3 years ago

Let xyz be the number

x = 2y

j = y-15

y=j+15

k=x+y

k= 2y+j+15

k = 2(j+15)+j+15

k = 2j+30+j+15

k = 3j+45

• Login to reply the answers
• Philip
Lv 6
3 years ago

Last sentence in question should end in "relationship between j and k?".

The 3 numbers are p,q,j.

p = 2q.

j = q -15.

k = p + q.

p = 2q = 2(j + 15) = 2j + 30.

q = j + 15.

k = p + q = (2j + 30) + (j + 15) = 3j + 45 = 3(j + 15).

Choice D pertains.

• Login to reply the answers
• ?
Lv 7
3 years ago

Let's use h, i, j as the 3 numbers

> k is the sum of the first two numbers

TRANSLATION: k = h+i.......................[1]

> the first number is twice the second number,

TRANSLATION: h = 2i.........................[2]

> the third number is 15 less than the second number.

TRANSLATION: j = i-15.......................[3]

So we have 3 equations to work with:

k = h+i...............[1]

h = 2i.................[2]

j = i-15...............[3]

Equation [3] can be rewritten solving for i:

.....j = i-15...............[3]

.....j+15 = i

.....i = j+15..............[3a]

The relationship between j and k is found as follows:

Starting with [1], substitute for h from [2] into [1]

.....k = h+i........[1]

.....k = (2i)+i

.....k = 3i..........[4]

The relationship between k and j is found by

substituting for i from [3a] into [4]

.....k = 3(j+15)

.....k = 3j + 45................ANS (Option D)

• Login to reply the answers
• How do you think about the answers? You can sign in to vote the answer.
• 3 years ago

Let j be the first number

then the second number is j+15

and the first number is 2j+30

The sum of the first two numbers is 3j+45

so k = 3j+45

• Login to reply the answers
Still have questions? Get your answers by asking now.